AN ASSESSMENT ON THE EMPOWERMENT OF LOCAL GOVERNMENTS - Çetin, Mehmet Sirin (Güneydogu Arastirmalari Dernegi, 2025)
As people started to live together, the need to fulfill some common services arose. It is possible to argue that local governments were born as a result of the search for the fulfillment of these needs. Local democracy is a model of democracy, which can be defined as ‘the government of the people’ at the local level. Today, due to the increasing importance of democracy, the strengthening of local governments is discussed as an important issue. As a matter of fact, the strengthening of local governments is of great importance since it reinforces the importance of democracy. In order to be able to talk about a strong local government, it is thought that it is important to ensure the effective participation of citizens living in the local government unit to the administration, to ensure that the local government unit is strong in terms of resources, to ensure that the services provided to the public are effective and efficient, to equip the local government unit with technological facilities and to increase the opportunities for local cooperation. In light of these explanations, the study aims to reveal the importance of the subject by utilizing theoretical sources.

Insanlarin bir arada yasamaya baslamalari ile ortak bazi hizmetlerin giderilmesi ihtiyaci dogmustur. Bu ihtiyaçlarin giderilmesi için girisilen arayislarin sonucunda yerel yönetimlerin dogdugunu savunmak mümkündür. Öz bir tanimlama ile ‘halkin yönetimi’ seklinde tanimlanabilecek olan demokrasinin yerel düzeyde uygulama modeline yerel demokrasi denilebilmektedir. Günümüzde demokrasinin artan öneminden dolayi yerel yönetimlerin güçlendirilmesi önemli bir konu olarak tartisilmaktadir. Nitekim yerel yönetimlerin güçlendirilmesi demokrasinin öneminin perçinlenmesi anlamina geleceginden önem arz etmektedir. Güçlü bir yerel yönetimden bahsedilebilmesi için yerel yönetim biriminde yasayan vatandaslarin yönetime etkin katiliminin saglanmasi, yerel yönetim biriminin kaynaklar açisindan güçlü olmasi, halka sunulan hizmetlerin etkin ve verimli olmasi, yerel yönetim biriminin teknolojik imkânlarla donatilmasi ve yerel isbirligi olanaklarinin artirilmasi gibi olanaklar bakimindan iyilestirmelerin önemli oldugu düsünülmektedir. Bu açiklamalar isiginda çalisma teorik kaynaklardan faydalanarak konunun önemini ortaya koymayi amaçlamaktadir.
YEREL YÖNETIMLERIN GÜÇLENDIRILMESI ÜZERINE BIR DEGERLENDIRME
Keywords: Public Administration; Kamu Yönetimi